EFFECTIVENESS AND EFFICIENCY OF THE IMPLEMENTATION OF NON-CASH FOOD ASSISTANCE PROGRAM IN LABUHAN LOMBOK VILLAGE - Ida Ayu Nursanty; Agus Khazin Fauzi; Reni Selpiana (Fakultas Agama Islam Universitas Islam Al-Azhar, 2024)
This study aims to empirically test the effectiveness and efficiency of implementing the Non-Cash Food Assistance Program (BPNT) in Labuhan Lombok Village, East Lombok Regency. The type of research used in this research is quantitative descriptive. Data collection techniques used in this study are questionnaires and interviews. The results of this study indicate that the effectiveness and efficiency of the implementation of the Non-Cash Food Assistance Program (BPNT) social assistance in Labuhan Lombok Village, East Lombok Regency on the effectiveness variable is 67.54%, and the efficiency variable is 66.13%. Implementing the Non-Cash Food Assistance Program (BPNT) in Labuhan Lombok village is categorized as quite effective and relatively efficient. However, regarding the effectiveness variable, there are still indicators that the rules, such as indicators on time, have not been achieved. Meanwhile, there are still indicators in the efficiency variable that the regulations, such as time efficiency indicators, have not been completed.